ANALISIS PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT CAHAYA MULIA TOYS - Yayan Yanuari (Scientium Management Review, 2023)
This study aims to determine the factors that affect the performance of employees at PT. Cahaya Mulia Toys. These factors are motivated crimes and the working environment. Employees who have the motivation and a good working good working environment will have a positive impact to the organization, so as to achieve organizational goals. The purpose of this study was to determine the influence of motivation and work environment on employee performance. Data collection method used is by interview and questionnaire to the respondent. Data were analyzed using quantitative method and descriptive method. The results of the research showed that the regression coefficient of Y = -11.032 + 0.62X₁ +0.71X₂. Means if no policy on work motivation (X₁ = 0) and work environment (X₂ = 0), then the employee performance (Y) amounted to-11.032. while if the increased work motivation (X₁ = 1), The performance of employees (Y) will be increased by 0.62 and if the work environment improved (X₂ = 1), the performance of employees (Y) will be increased by 0.71. From the calculation of multiple correlation coefficient is that the value r1y = 0,879, these results suggest that there is a strong and positive relationship that the work motivation (X₁) on employee performance (Y). R2y value = 0,656 these result indicate that there is a strong correlation between the positive and work environment (X2) on employee performance (Y). The correlation coefficient between work motivation (X₁) and working environment (X₂) on employee performance (Y) by 0.879. value determination coefficient Kd = 77.26% Based on the results of hypothesis testing using t-test statistical analysis, the value of t1 count equal to 9.765> t table 2.048. means Ha accepted and Ho rejected. And the significance of influence and relationships work environment on employee performance is obtained t2 count of 4.599 > 2.048 means Ha accepted and Ho rejected. While the result of calculations using analysis f test values obtained f hitung 45.87 > f table values of 3.35, means Ha accepted and Ho rejected. Thus it can be concluded that motivation and work environment together have an influence on the performance of employees of PT. Cahaya Mulia Toys.